Authorship Attribution: Specifics for Slovene - Zwitter Vitez, Ana (Slavia Centralis, 2020)
The paper shows the importance of a quality analysis of linguistic features which enable the process of authorship attribution or author profiling in a forensic, literary or economic context (anonymous threat letters, plagiarism, literary works of unknown authorship, client profiling). It also highlights the lack of realized analyses for Slovene and outlines the methodology of detecting the syntactic, lexical, semantic and character features in order to quantify the author’s personal style.